Comprehensive analysis of whole genome methylation in mouse blastocysts cultured with four different constituents following in vitro fertilization - Yu Horibe; Kazuhiko Nakabayashi; Miyuki Arai; Kohji Okamura; Kazunori Hashimoto; Hideo Matsui; Kenichiro Hata (Middle East Fertility Society Journal, 2019)
Abstract Background With the development of assisted reproductive technology (ART), diseases believed to be caused by ART have begun to be identified as imprinted disease. However, no conclusion has been reached. So we sought to determine whether ART procedures disturb gene methylation and whether imprinted genes alone are selectively disturbed. To examine whether the constituents of the culture medium contribute to the changes in methylation, we used a mouse model to conduct IVF and comprehensively analyzed 5′–C–phosphate–G–3′ (CpG) by reduced representation bisulfite sequencing (RRBS) using a second-generation sequencer to determine changes in methylation using four types of culture media with different amino acid constituents. Results We cultured ova to the blastocyst stage in a mouse model in culture media with four different amino acid constituents. Each culture medium included (1) KSOM culture medium (NoAA), (2) KSOM media + essential amino acids (EAAs), (3) KSOM medium + non-essential amino acids (NEAAs), or (4) KSOM medium + EAAs + NEAAs (AllAA) analyzed by reduced representation bisulfite sequencing. The results showed that (1) there were many regions that maintained hypermethylation with NEAAs, (2) there was little effect of demethylation on reprogramming in the 5′UTR and promoter regions, and (3) specific changes were observed in imprinted genes such as Nnat and Nespas. Conclusions Compared with EAAs, NEAAs could protect genes from demethylation caused by reprogramming. On the imprinted genes, methylation of the promoter region of H19 was decreased by NEAAs, suggesting that specific genes were prone to changes in methylation. It was suggested that these changes could provide similar results in humans. Further studies are needed to understand how changes in methylation may affect gene expression profiles.